Introducing GPS in fleet management of a mine: Impact on hauling cycle time and hauling capacity - Chaowasakoo,P. (Inderscience Enterprises Ltd., 2015)
Copyright © 2014 Inderscience Enterprises Ltd. Economics have significantly changed the way people think about work processes in several sectors, especially the mining industry. Mining companies search for suitable technologies to improve key operational areas, as operating processes efficiency is important to production economics. Many prior research studies indicate that hauling cost accounts for more than 50% of the total operational cost in open-pit mines. Therefore, in line with these findings, the purpose of this paper is to examine the benefits from applying a global positioning system (GPS) to a coal hauling operation in Indonesia. Understanding the strategic potential of GPS technology adoption in mining industries requires knowledge of actual working methods. One also needs to understand the process of simulation which is formulated by constructing mathematical models to represent working methods. Once the simulation is obtained, it can explain changing or unexpected circumstances in the mine, and support decisions for solving problems in mining operations.